2015 proceedings of the Conference on Control and its Applications (CT) 8-10 July 2015, Paris, France - Bonnet, Catherine; Pasik-Duncan, Bozenna 1947-; Özbay, Hitay; Zhang, Qing (Society for Industrial and Applied Mathematics, SIAM, 2015)
The field of control theory is central to a wide range of aerospace, energy, automotive and advanced technological systems and is increasingly recognized as fundamental for emerging fields ranging from nanotechnology, smart grid to cell regulation. Moreover, in addition to its traditional ubiquity in process regulation for the physical sciences and engineering, control concepts now pervade the biological, computer, and social sciences. This conference showcases a wide range of topics in control and systems theory. The topics and applications include control of PDEs, computational mathematics for control and optimization, real-time optimization and data assimilation, cooperative control for unmanned autonomous vehicles, differential games, cellular and biological regulation, control of hybrid systems, control techniques for financial mathematics, biomedical control, risk sensitive control and filtering, control of smart systems, flow control and quantum control
Keywords: Automatic control; Congresses; Discrete mathematics and graph theory; Konferenzschrift